2016
DOI: 10.1037/xge0000236
|View full text |Cite
|
Sign up to set email alerts
|

How does not responding to appetitive stimuli cause devaluation: Evaluative conditioning or response inhibition?

Abstract: In a series of 6 experiments (5 preregistered), we examined how not responding to appetitive stimuli causes devaluation. To examine this question, a go/no-go task was employed in which appetitive stimuli were consistently associated with cues to respond (go stimuli), or with cues to not respond (either no-go cues or the absence of cues; no-go stimuli). Change in evaluations of no-go stimuli was compared to change in evaluations of both go stimuli and of stimuli not presented in the task (untrained stimuli). Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
259
9
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(306 citation statements)
references
References 66 publications
(138 reference statements)
32
259
9
6
Order By: Relevance
“…Such a prolonged period of food cue exposure with response prevention could be considered highly atypical whereas approaching pleasant foods may best represent how we naturally interact with these foods. A recent study provides some support for this idea – participants undergoing a similar observe-control condition showed significantly greater devaluation of ‘go’ food stimuli than participants who had to respond to these foods in a go/no-go task (Chen et al., 2016). This occurred in the absence of increased valuation of go-images in some experiments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such a prolonged period of food cue exposure with response prevention could be considered highly atypical whereas approaching pleasant foods may best represent how we naturally interact with these foods. A recent study provides some support for this idea – participants undergoing a similar observe-control condition showed significantly greater devaluation of ‘go’ food stimuli than participants who had to respond to these foods in a go/no-go task (Chen et al., 2016). This occurred in the absence of increased valuation of go-images in some experiments.…”
Section: Discussionmentioning
confidence: 96%
“…Just as it has been argued that inhibition training may reduce food consumption by encouraging the development of stimulus-stop associations and activating an aversive centre, it is also possible that go training may encourage the development of stimulus-go associations and activation of an appetitive centre (McLaren and Verbruggen, 2016, Verbruggen et al., 2014b, Verbruggen et al., 2014a). Indeed recent findings suggest that in some experiments, go-associated food stimuli show an increase in valuation (relative to untrained food stimuli) after go/no-go training (Chen, Veling, Dijksterhuis, & Holland, 2016). This go-training effect may have contributed to effects of food inhibition training shown in previous studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two potentially critical factors are the percentage of items that were paired with targets (50% in Experiments 1-3 and 25% in Schonberg et al, 2014) and the amount of time that participants had to respond (1000 ms in Experiments 1-3 and ~380 ms in Schonberg et al, 2014; see also Bakkour et al, 2016). Though target frequency may not modulate the attentional boost effect , it may influence the effects of targets on the perceived value of concurrently presented items, particularly when response periods approach 1 s in duration (Chen, Veling, Dijksterhuis, & Holland, 2016). Given these considerations, it would be interesting to explore how target frequency and response deadline manipulations in the attentional boost effect paradigm influence the effects of target detection on perceived value and memory.…”
Section: Discussionmentioning
confidence: 99%
“…During food go/no-go training, visual (e.g., the border of a picture turning bold [16••]) or auditory go or no-go cues (e.g., a low tone [17••]) are presented in close temporal proximity to images of food items. Participants are instructed to press a button when a go cue is presented and to not press a button when a no-go cue is presented.…”
Section: What Is Food Go/no-go Training?mentioning
confidence: 99%
“…It has been suggested that repeatedly not responding to specific food items during food go/no-go training (a) trains ‘top-down’ inhibitory control over food-related responses [11], (b) creates direct food item-stop associations, a form of ‘bottom-up’ or automatic inhibition (e.g., [30, 31]), or (c) reduces evaluations of the food items [14, 17••, 23]. Next, we will consider whether these mechanisms operate during go/no-go training, and whether they may explain the behavioral effects.…”
Section: Possible Mechanismsmentioning
confidence: 99%